The impact of digital transformation readiness on strategic decision effectiveness in higher education institutions: Mediating role of technological infrastructure capability - Alfadhel, Abdullah Mohammed; Kassim, Mohamad Shah Bin; Ashaari, Azmirul Bin; Mahar, Shaza (International Journal of Innovative Research and Scientific Studies, 2025)
This study examines the impact of digital transformation readiness on strategic decision effectiveness in higher education institutions (HEIs), with a focus on the mediating role of technological infrastructure capability. As the educational sector faces increasing pressure to innovate and adapt to evolving technological landscapes, understanding how digital readiness and infrastructure influence strategic decision-making has become essential. Employing a quantitative approach, this research explores the direct and indirect relationships among the variables. A structured survey was administered to 210 academic and administrative staff across selected public universities. Data analysis using PLS-SEM reveals a significant and positive relationship between the constructs. The findings emphasize that higher digital preparedness and robust infrastructure enhance the quality and effectiveness of strategic decisions. Implications for institutional policy and leadership are discussed.